Experimental Investigation of the Strength and Behavior of Reinforced Concrete Spandrel Beams Under Repeated Loads - Mohamad-Ali, Anis A.; Abdu-Alrazaq, Adi Adnan (Basrah Journal for Engineering Sciences, 2010)
The main objective of this study is to investigate the effect of repeated load on the strength and behavior of the spandrel beam by considering eight specimens divided into four groups based on the design methods; type of cross-section of the spandrel beam and the type of loading. Two design methods, two types of loading and two types of cross sel.1ions for spandrel beam are considered, the first is a solid rectangular section, while the other is a hollow rectangular section. The effect of repeated loads on the crack’s width, deflections, torque, and angle of twist is studied using two stages of loading, the first stage is at the soft-cracking stage after the occurring of cracks in the spandrel beam and the second stage is the yielding of the bottom longitudinal reinforcement of the floor beam.